Comparisons of draft gear damping mechanisms. Issue 4 (3rd April 2017) - Wu, Qing; Luo, Shihui; Qu, Tianwei; Yang, Xiangjian
ABSTRACT: This paper compared three types of draft gears with different damping mechanisms: friction, polymer and friction–polymer. Impact characteristics, frequency responses, in-train characteristics and fatigue damage for these draft gears were compared. Wagon impact simulations show that the friction draft gear, polymer draft gear and the friction–polymer draft gear can withstand impact speeds of 9, 12 and 11 km/h, respectively. Comparisons of frequency responses show that the friction draft gear has higher stiffness at lower working velocities, while the polymer draft gear has lower stiffness at lower working velocities. The response of the friction–polymer draft gear is less sensitive to the working velocities as it blends the friction and polymer damping mechanisms and offsets their influences on draft gear forces. Train dynamics simulations show that the in-train characteristics of friction draft gears and polymer draft gears are similar to their static characteristics and very different from their impact characteristics. The in-train characteristics of the polymer draft gears have lower stiffness and lower damping abilities than the other two types of draft gears. The friction–polymer draft gears achieved better vehicle acceleration performance than the friction draft gears. The polymer draft gears achieved similar maximum accelerations throughout the train and the maximum accelerations were significantly lower than that of the other two types of draft gears. The polymer draft gears achieved 23.4% less fatigue damage than the friction draft gears; the fatigue damage of the friction–polymer case is only half that of the friction case.